Studying Parameters of 24-Hour Blood Pressure Monitoring in Patients with Arterial Hypertension and Abdominal Obesity - Minovarova Charrazkhon Anvarovna; G. A. Atakhodjaeva (Scholars Digest Publishing, 2023)
The purpose of the study: to study the daily blood pressure profile in young patients with hypertension and against the background of abdominal obesity (AO). To achieve this goal, 99 patients with stage I-II hypertension were examined, including 59 men and 40 women aged 18-44 years. It has been established that the presence of AO contributes to disruption of the daily blood pressure profile in young hypertensive patients. In patients with hypertension and AO, the disturbance in the daily rise in blood pressure is mainly due to an increase in SBP, especially in the morning.
Keywords: abdominal obesity, young age, arterial hypertension, blood pressure.